Water quality surrounding to MSW dumps of Raipur city-A case study - Agrawal, Anita; Pandey, Rama; Agrawal, M L (Recent Research in Science and Technology, 2013)
In India, urbanization and rapid population growth have led to degradation of environment, by increased rate of exploitation of natural resources and generation of municipal solid wastes (MSW). Municipal Solid Waste (MSW) disposal is a big problem for most of the towns in developing countries. In India dumping of MSW on low laying area is the common practice in most of the towns. The dumping of waste in uncontrolled manner creates many kinds of problems for the surrounding environment. Ground water pollution is one of the serious effects of the MSW dumping. The assessment of impacts on ground water sources near to MSW dumps is of considerable importance in management and disposal of solid waste. The leachate may greatly affect the ground water sources near to the dumpsites. In the present study an attempt has been made to investigate the extent of impact on ground water sources namely open wells, shallow tube wells (depth less than 30 m) and deep tube wells (depth more than 50 m). The pollution status is also monitored at varying distances from the solid waste dumping sites to investigate the trend of leachate movement in the subsoil. Water samples from different sources at different locations are assessed for physical, chemical and biological properties.